A micro size terahertz wheel shaped antenna with non-defected ground structure - Swaminathan, Narayanan; Rajendiran, Murugesan (Institute of Advanced Engineering and Science, 2024)
A micro dimension antenna with wheel-geometrical wide-band terahertz (THz) is suggested in this research. In the circular shaped patch, concentric circle shaped slots are incorporated to form a wheel shaped patch antenna. The suggested model is designed on a polymide substrate with dielectric constant of 4.3 and thickness of 20 µm. The suggested prototype antenna is very much compact in size of 210×160 µm2 . The designed antenna achieves a wideband operation from 8.692 THz to 9.772 THz. This prototype antenna’s maximum realized gain is 10.2 dBi at 9.0 THz. This high gain is important for wide range of wireless applications. The radiation pattern, radiation efficiency, reflection coefficient, surface current distribution and voltage standing wave ratio are examined through the simulation results. In future video rate imaging system, super fast close-range in-door wireless communication, biomedical picturing, homeland defence equipments, security scanning, explosive detection, and characterisation of materials in the THz level will be benefited from the suggested THz antenna.